Traction Performance Analysis of Track Wheels Type on Wet and Deep Muddy of Soil in Soil Bin - Muhammad Taufiq; Tineke Mandang; Wawan Hermawan; Desrial (Jurnal Keteknikan Pertanian, 2022)
Hand tractors with lugged wheels have difficulty when operating in wet and deep mud of paddy fields. To solve this problem, the wheels need to be replaced with tracks wheel type that have a much larger contact area. Data on traction performance characteristics of the track wheel type on muddy soil are required for design purposes, which can be obtained by testing the prototype of track wheel type on a soil bin. The objective of this research is to analyze the traction performance of the lugged track of wheel type on wet soil. The track wheel type with a length of 60 cm and a width of 20 cm will be tested in a soil bin filled with wet and muddy soil with a depth of 30 cm. The test will be carried out on variations in vertical loads of 9.5, 12.5, 15.5, 18.5, and 22.7 kg; horizontal loads of 1, 2, 3, and 4 kg; distance between of lugs of 12.70, 19.05, and 25.40 cm; and height of lugs of 5, 10, and 15 cm. Parameters observed in the test are sinkage, slip and traction efficiency. The test results show that the pull force and vertical force have a dominant effect on track sinkage, track slip, and tractive efficiency. The optimum track wheel type design has size a lug height of 10 cm and a distance between lugs of 19.05 cm result in a sinkage of 7.32 cm, slip of 14%, and tractive efficiency of 68.46%.